'This is ridiculous – I need to start a paper…': An exploration of aims and intentions of regional print proprietors of post-COVID start-up newspapers. (August 2022) - Barnes, Renee; Dugmore, Harry; English, Peter; Natoli, Rosanna; Stephens, Elizabeth J
In May 2020 at the height of Australia's first national COVID lockdown, NewsCorp Australia announced that more than 125 regional newspapers would either be closed or become available online-only. Queensland was hit hard with 22 regional and 20 community newspapers shifting to online formats, and 15 community newspapers closing. Yet within months of the NewsCorp changes, a significant number of new print newspapers were being announced to fill the 'news deserts'. Broadly welcomed by those in these local communities, the new publications suggest a reinvigoration of long-standing norms and tenets, many of which are specific to regional print news media, such as community-centred, locally-shaped news values and high reliance on 'micro-ads' (i.e. classifieds) and hyper-local business revenue. But given the dire prognostications about print business models, what are the aims and intentions of these start-ups (n = 22), and how do they translate their notions of community-centric news into business models they perceive as viable? Drawing on Hanitzsch and Vos framework for the discursive constructions of journalists' role in society, we find these newspaper start-ups both reassert and claim more vigorously the normative values associated with community journalism as 'social glue', while also developing 'lean start-up' business models that capitalise on the sense of a local newspaper's 'social good' functions through an affective rationale. We argue this represents a shift to a new 'hybrid' model, with strong elements of a traditional and still feisty monitorial news values fusing with a more 'morale-enhancing' and explicitly social cohesion-centric role conceptions. We call it a 'community cohesion model'.